Woman sitting on a porch in Washington, D.C. - Murrow, Janet Brewster (Tufts Archival Research Center, 2014)
This date is approximate. negatives (photographic). This may be Blanche Paley Levy, Dr. Leon Levy's wife and William S. Paley's sister.